Blood promise - Mead, Richelle (New York : Razorbill, 2009)
Just days before graduating from St. Vladimir's Academy, guardian-in-training Rose travels to Siberia to drive a stake into the heart of the boy she loves, the monstrous vampire Dimitri.
Keywords: Vampires -- Juvenile fiction; Supernatural -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Siberia (Russia) -- Juvenile fiction; Russia (Federation) -- Juvenile fiction